Objetivación e inferencia arqueológicas como proceso lógico del conocimiento histórico. - Carbonell, Eudald; Vaquero, Manuel; Pastó, Ignasi; Rodríguez, Xose Pedro; Sala, Robert (Complutum, 1996)
Sin resumen